Benign Duodenal Stricture Treated with Surgical Correction and Dietary Therapy in a Golden Retriever - John C. Rowe; Alice A. Huang; Jin Heo; Nolie K. Parnell; Adam J. Rudinsky (Case Reports in Veterinary Medicine)
A benign duodenal stricture is a well-documented condition of humans that has not been characterized in dogs. In this case report, the clinical, radiographic, ultrasonographic, endoscopic, surgical, and histopathologic findings of a single benign duodenal stricture in a Golden Retriever are reported. Definitive diagnosis was made possible with the utilization of esophagogastroduodenoscopy (EGD). Surgical correction of the stricture, paired with dietary therapy that utilized a highly digestible diet, resolved the clinical signs in the case reported. Several inciting causes were identified as possible drivers of stricture formation, including nonsteroidal anti-inflammatory drug (NSAID) administration, mucosal ulceration, traumatic injury, or inflammatory intestinal disease. A benign duodenal stricture should be considered an infrequent cause of intermittent, chronic gastrointestinal signs that may have a favorable outcome via surgical correction and dietary management.